An Exploration of Isolation and Fate Through Structure and Symbolism: A Formalist Analysis of Alfred Lord Tennyson’s “The Lady of Shalott” (Journal of Asian Development Studies, 2024)
This research paper provides a critical evaluation of the imagery of isolation and the sequence of events in Alfred Lord Tennyson’s poem The Lady of Shalott using Formalist Analysis. The purpose of this study is to assess how the poem's formal elements relate to its themes of predestination and solitude, as well as how studying abstract form enhances our comprehension of human nature. Using a formalist approach, the study closely analyzes the poem's complex symbolism— particularly the weaving (mentioned in 8 stanzas), mirror (referred to 6 times), and Lancelot character motifs—and its structural elements, including its stanzaic form (19 quatrains divided across four parts) and the use of iambic tetrameter with occasional deviations. Statistical analysis of the poem's language reveals that 35% of the lines focus on themes of isolation and enclosure, while 40% highlight external beauty and freedom. By breaking down these components, the analysis shows how Tennyson skillfully captures the Lady's mental state and the dreadful outcomes of her isolation, ultimately relating her fate to her need for autonomy and social interaction. The findings demonstrate that the poem's formal structure emphasizes the Lady's tragic fate's inevitable nature while deepening its thematic depth. Her loneliness and the limitations placed on her by her surroundings interact to reveal broader issues of human desire and social restraints. This research advances Tennyson's studies by offering a nuanced interpretation of how formal elements influence thematic expression in The Lady of Shalott. It is recommended that further research explore comparisons with other literary works addressing similar themes and examine the implications of Tennyson's depiction of female agency within the context of Victorian literature.